ETNOBOTANI TUMBUHAN KUNYIT (CURCUMA LONGA) DI DESA OINLASI MOLLO SELATAN KABUPATEN TIMOR TENGAH SELATAN (TTS) - Delfin Margerita Lake; Andam Suriaty Ardan; Moses Kopong Tokan; Mario J Santrum (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aimed to determine community knowledge and ethnobotanical utilization of turmeric (Curcuma longa) in Oinlasi Village, South Mollo District, Timor Tengah Selatan Regency. This research used a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. Respondents were selected using purposive sampling, consisting of community members who have knowledge and use turmeric in their daily lives. The results showed that the people of Oinlasi Village have good knowledge of turmeric and utilize it in various aspects of life. The most commonly used plant part is the rhizome. Turmeric is used as traditional medicine to treat stomachache, wounds, and inflammation, as a cooking spice, and in certain traditional ceremonies. The processing methods include pounding, boiling, or grating depending on the purpose of use. Knowledge of turmeric utilization is inherited from generation to generation through oral tradition. In conclusion, turmeric (Curcuma longa) plays an important role in the lives of the Oinlasi community in terms of health, food, and cultural practices. This ethnobotanical knowledge needs to be preserved as part of the local wisdom of the community.